Invasioni biologiche. Il caso drammatico delle palme e di due specie di insetti, il Punteruolo rosso delle palme (Rynchophorus ferrugineus, Coleotteri) e il castnide delle palme (Paysandisia archon, Lepidotteri) in Italia (Altre Modernità, 2013)
The biological invasions represent today a serious ecological problem, and is one of the main threats to biodiversity, in Italy as in the rest of the world. In the last century several species of palm trees have been introduced in gardens, parks and lanes of great part of Italy, where climate allows their life and growth. Among the others Phoenix canariensis, P. dactylifera, Washingtonia robusta, W. filifera, Jubaea spectabilis and Trachycarpus fortunei. All of these species are exotic, as the only indigenous palm in Italy is the dwarf fan palm (Chamaerops humilis), which occurs along the tirrenian coast from Sicily to Liguria, in Sardinia and most of the smaller islands. Palm trees have become by now part of the Italian landscape, as do pine tree in Rome or cypress in Tuscany. Recently, two different species of exotic insects where recorded for the first time in Italy: the south American moth Paysandisia archon and the chinese beetle Rhynchophorus ferrugineus. Both of them lay their eggs on palm trees, and their larvae feed into the stem and kill the palms. Both arrived in Italy and in other Mediterranean countries as larvae or eggs hidden into the plants imported from the native regions. These insects are rapidly spreading through Italy, following palm plantations, and destroying palms from north to south, with a huge economic damage. Furthermore, they are locally changing probably for ever the Italian landscape. More recently, there is evidence of infestation on dwarf fan palm by both the moth and the beetle. This could cause a local extinction of the palm.